Study of the production and distribution of middle horizon pottery of Cuzco, Perú by k_0-based instrumental neutron activation analysis - Montoya, Eduardo (2002)
The objective of the present research was to establish, in general terms, the provenience of certain pottery styles dating to the Middle Horizon which are known to the Southern Highlands, Cuzco region. The specific goal was to determine which of these ceramic styles were made in other regions and brought to Cuzco and which were imitations locally manufactured, and to compare their patterns of production and distribution with those of local ceramic styles. These data, in turn, being helpful for understanding some aspects of the social, economic and political dynamics of the Middle Horizon period at Cuzco.